Team leadership and environmental motivation in university administrative management. - Gómez Bernett, Jenny Del Socorro; Bernal Payares, Omaira (Universidad Francisco de Paula Santander, 2015)
This research develops a global theory that integrates and describes environmental motivation, team leadership and administrative management in public universities. The aim is to promote the importance of inciting and institutionalizing an adequate environmental behavior in the university strata, recognizing team leadership, environmental motivation and academic-administrative management as a fundamental tool to achieve it. The research takes place at the University of Cartagena, in the period 2011-2013, in a stratified sample (staff teachers, professors, contractor workers, staff workers and students) with a total of 378 people. The results of this research will be relevant for the development of the Institutional University Environmental Management Plan. The analysis of the results shows that universities, in compliance with their environmental social responsibility, mission and vision, should apply and lead strategies to significantly improve the behavior and environmental awareness of the university society, since these two factors constitute a determining deficiency in the harmonization of team leadership, university environmental motivation and administrative management.